2013
DOI: 10.1371/journal.pone.0056943
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-Temporal Clusters and Risk Factors of Hand, Foot, and Mouth Disease at the District Level in Guangdong Province, China

Abstract: ObjectiveHand, foot, and mouth disease (HFMD) has posed a great threat to the health of children and become a public health priority in China. This study aims to investigate the epidemiological characteristics, spatial-temporal patterns, and risk factors of HFMD in Guangdong Province, China, and to provide scientific information for public health responses and interventions.MethodsHFMD surveillance data from May 2008 to December 2011were provided by the Chinese Center for Disease Control and Prevention. We fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
150
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(182 citation statements)
references
References 28 publications
26
150
2
4
Order By: Relevance
“…However, no spatial clustering studies of the incidence of severe HFMD or the proportion of severe HFMD cases among total HFMD cases have been conducted. Several studies have reported spatial clustering of the incidence of general HFMD (7)(8)(9)(10)(11), although all previous studies of HFMD clusters used district-level incidence data, which might have masked the potential effect of local environment. Thus, we analyzed the incidence of severe HFMD and the proportion of severe HFMD among total HFMD cases at the township level, which facilitated evaluation of the link between severe HFMD and environment factors at a higher geographical resolution.…”
Section: Introductionmentioning
confidence: 99%
“…However, no spatial clustering studies of the incidence of severe HFMD or the proportion of severe HFMD cases among total HFMD cases have been conducted. Several studies have reported spatial clustering of the incidence of general HFMD (7)(8)(9)(10)(11), although all previous studies of HFMD clusters used district-level incidence data, which might have masked the potential effect of local environment. Thus, we analyzed the incidence of severe HFMD and the proportion of severe HFMD among total HFMD cases at the township level, which facilitated evaluation of the link between severe HFMD and environment factors at a higher geographical resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Younger age (<5 years) predominance was related to the differences in serum antibodies according to age groups. 4 Additionally, a seroprevalence study from Germany reported that 66% of children aged 1-4 years did not posses neutralizing antibodies to CV-A16. 11 Since 2004, there has been an increase in the number of reports of a more severe form of HFMD associated with CV-A6.…”
Section: Resultsmentioning
confidence: 99%
“…4 In another study 89.75% of HFMD patients were aged <4 years. 8 Other studies confirmed the younger age (<5 years) and HFMD cases due to CV-A6 during an outbreak between 2011 and 2012 in North America.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In order to nurture a healthy, intelligent and active pupil; efforts are needed to empower them so that they can be responsible for their own health. Therefore, hygiene promotion is the main focus of the policymakers to reduce the occurrence of infectious disease (Curtis, S. Cairncross, & R. Yondi, 2000;Te et al, 2013).…”
Section: Introductionmentioning
confidence: 99%